2022
DOI: 10.1111/cen.14675
|View full text |Cite
|
Sign up to set email alerts
|

Age increased the cancer‐specific mortality risk of thyroid cancer with lung metastasis

Abstract: Background: To investigate the relationship between age and cancer-speci c mortality in thyroid cancer (TC) with lungmetastasis.Methods: 1,418 patients with initial distant metastases from Surveillance, Epidemiology and End Results databases were investigated. Patients with median follow-up time of 8 months [interquartile range (IQR), 2-27] and median age of 66 years (IQR, were divided into ve groups by age and the association between age and TC-speci c mortality was analyzed.Results: The TC-speci c mortality … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(86 reference statements)
1
3
0
Order By: Relevance
“…Age, sex, and tumor size are established prognostic factors in differentiated thyroid cancer. Previous studies indicated that patients over 55 years have a poorer response to RAI therapy (32) and a worse overall prognosis (33) in thyroid cancer with lung metastases, with mortality rates increasing with age (34). Consistent with these findings, the average age of patients in RAI-refractory group were 5 years older (P <0.05) than those in RAI-avid group in the primary cohort.…”
Section: Discussionsupporting
confidence: 69%
“…Age, sex, and tumor size are established prognostic factors in differentiated thyroid cancer. Previous studies indicated that patients over 55 years have a poorer response to RAI therapy (32) and a worse overall prognosis (33) in thyroid cancer with lung metastases, with mortality rates increasing with age (34). Consistent with these findings, the average age of patients in RAI-refractory group were 5 years older (P <0.05) than those in RAI-avid group in the primary cohort.…”
Section: Discussionsupporting
confidence: 69%
“…Age, sex, and tumor size are established prognostic factors in differentiated thyroid cancer. Previous studies indicated that patients over 55 years have a poorer response to RAI therapy ( 32 ) and a worse overall prognosis ( 33 ) in thyroid cancer with lung metastases, with mortality rates increasing with age ( 34 ). Consistent with these findings, the average age of patients in RAI-refractory group were 5 years older (P <0.05) than those in RAI-avid group in the primary cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Huang et al [5] found that increasing age further influenced the occurrence and progression of PM in TC patients. Similarly, age at diagnosis was identified as an independent predictor of PM in patients with NPTC in the present study, and the mean age at disease increased by approximately 10 years in patients with NPTC who developed PM than in those who did not.…”
Section: Discussionmentioning
confidence: 99%